Linearization of the Sobolev and Babeyko’s formulae for transformation of P-wave velocity to density in the Carpathian-Pannonian Basin region - CSICSAY, Kristián; BIELIK, Miroslav; MOJZEŠ, Andrej; SPEVÁKOVÁ, Eva; KYTKOVÁ, Bibiána; GRINČ, Michal (Contributions to Geophysics and Geodesy, 2012)
The initial density model has to be based on a reasonable geological hypothesisand while the modelling process is non-unique, one of the interpretation aims is to definethe robust parameters of the model. It is important at this stage to integrate the seismicand gravity data. One of the possibilities how to integrate these data is transformationof the seismic velocities to densities. The Sobolev and Babeyko’s formulae belong to themost available relationships for this transformation. They are very complex and rigoroustaking into account the PT conditions. On the other hand its application is relativelycomplicated. Therefore the main goal of the paper is to try to determine more easily theformula for transformation of the seismic velocities to densities. Based on the analysisof the results obtained using the Sobolev and Babeyko’s formula on real data, we foundout that in the Carpathian-Pannonian Basin region this formula can be transformed tosimpler linear velocity–density relationship with required accuracy.